Calculating intraocular lens power in anterior megalophthalmos: A case report - Mu, Jiancheng; Yang, Yu; Xiong, Tianxu; Fan, Wei (Frontiers in Medicine, 2022)
Introduction: We report a case in which some myopia was retained when calculating intraocular lens (IOL) power using the Haigis formula in order to avoid postoperative farsightedness in a man with cataract and anterior megalophthalmos (AM). Case description: A 59-year-old Chinese man was referred to our clinic for cataract surgery in his right eye. He had strong bilateral megalocornea, and his left eye had undergone surgery four times. After complete preoperative examinations and repeated biometry, the Haigis formula was used and a 3-piece IOL was implanted with a target power of -1.97 D. At one-year follow-up, the patient showed best corrected distance vision of 20/20 with refraction of -1.50 DC × 160°, and the IOL was stable. Conclusion: Our patient with anterior megalophthalmos showed postoperative hyperopia drift even though the Haigis formula was used as suggested in previous studies. In order to prevent farsightedness after surgery, some myopia should be retained when calculating IOL power. The Kane, Holladay II with AL adjustment and Barrett Universal II formulas may be more accurate for calculating IOL power in such patients.